Fact Checking and Information in the Age of Covid. Issue 3 (4th September 2020) - Seaton, Jean; Sippitt, Amy; Worthy, Ben
Abstract: The Covid‐19 pandemic has revealed and accelerated an information crisis as well as a health one. What we discover about Covid 19, how it spreads, to whom and why and how best to mitigate it—all depend on information. The essays in this special section, which this article introduces, explore the importance of information and the fundamental role of fact checkers in understanding how information flows, why mistakes are made, and how to counteract them. Fact checking as an idea and a practice emerged in the early twenty‐first century, developed as a positive beacon to counteract a growing sense that information could no longer be trusted. Now, more than a decade after its creation, fact checking sits within a far more complex and chaotic media context, and its expertise and understanding has never been so important. We need to understand what fact checkers do because they are grappling with how to tether us to reality.